Risk Factors for Mortality and Pre-ICU Fluid Balance Among Critically Ill Hematopoietic Stem Cell Transplant Patients. (November 2020) - Mueller, Dana M.; Markovitz, Barry P.; Zinter, Matt S.; Takimoto, Sarah W.; Khemani, Robinder G.
Objective: To examine if fluid balance surrounding pediatric intensive care unit (PICU) admission in hematopoietic stem cell transplant (HSCT) patients was associated with mortality, ventilator-free days, and intensive care unit (ICU)-free days. To explore other population-specific factors associated with poor outcome. Materials and Methods: Retrospective review of HSCT patients admitted to 2 quaternary PICUs, Children's Hospital Los Angeles and University of California San Francisco Benioff Children's Hospital from January 2009 to December 2014. Results: Of 144 patients, 92 were identified with complete fluid balance data available. No difference in fluid balance between survivors and nonsurvivors in the 24 hours preceding PICU admission ( P = .81) or when the first 24 hours of PICU stay were taken into account ( P = .48) was identified. There was no difference in ventilator-free or ICU-free days. Comparing Pediatric Index of Mortality (PIM)-2, Pediatric Risk of Mortality (PRISM)-3, and a multivariable model using independent risk factors identified through multivariable analysis, the receiver operating characteristic plot for the multivariable model (area under the curve = 0.844 [95% confidence interval: 0.77-0.92]) was superior to both PIM-2 and PRISM-3 in discriminating mortality. Conclusions: Fluid balance immediately preceding and early in the course of admission was not associated with mortality in PICU HSCT patients. A subset of variables was identified which better discriminated mortality in this cohort than accepted PICU severity of illness scores.